PENDAMPINGAN PEMASARAN PRODUK DAN PELATIHAN PENYUSUNAN PEMBUKUAN SEBAGAI UPAYA PENINGKATAN PENDAPATAN PADA KELOMPOK USAHA DUPA CENDANA DI DESA PED, KECAMATAN NUSA PENIDA - Ni Komang Sumadi; I Gede Aryana Mahayasa; Putu Deddy Samtika Putra; I Kadek Yogi Dwi Astina; Ni Kadek Evita Noviantari (JURNAL SEWAKA BHAKTI, 2023)
The Cendana Incense Business Group is located in Ped Nusa Penida Village and has been running for 3 years serving incense orders around Ped Nusa Penida Village. The sandalwood incense business group consists of 3 groups, each group consisting of 6 Ped Village residents who do not have a job. The production process of sandalwood incense is very smooth in fulfilling the orders it receives. In carrying out Hindu religious ceremonies in Bali, incense is a very important and necessary ceremonial tool. So, incense is one of the staple ingredients in religious ceremonies in Bali. Based on observations made in Nusa Penida District, so far, the people of Nusa Penida have ordered/purchased incense in mainland Klungkung both for direct use and for resale/marketing. This is caused by ignorance of good and correct product marketing strategies. To help overcome these problems, this service activity will be more focused on providing product marketing assistance in an effort to increase opinion and training in the preparation of good and correct bookkeeping. The group that has been formed is expected to be able to produce incense in large quantities so that it is hoped that in the future the sandalwood incense business group will be able to meet market demand in Nusa Penida District. This service activity also provides marketing strategy assistance so that it is hoped that in the future it will be able to market incense products that produce very well through social media that are currently developing. The results achieved in this service are that the sandalwood incense business group has been able to produce incense in large quantities and from now on they have sufficient knowledge to market their products properly and immediately practice making good and correct simple corporate financial accounting reports. Assistance activities like this are still very much needed by these business groups. Evaluation of this activity will be carried out again after seeing the business development of these groups.